Kate in waiting - Albertalli, Becky 1982- (Balzer + Bray, an imprint of HarperCollinsPublishers, 2021)
Best friends Kate Garfield and Anderson Walker share a love of theater and crushes on the same guys, but when one of their long-distance crushes shows up at their school, real feelings might end their friendship